1997
DOI: 10.1016/s0006-3495(97)78295-x
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of creatine phosphokinase and beta-enolase in cultured muscle cells

Abstract: The diffusion of beta-enolase and creatine phosphokinase in muscle cells has been studied by modulated fringe pattern photobleaching. Beta-enolase is mobile in the sarcoplasm. At 20 degrees C, the diffusion coefficient is 13.5 +/- 2.5 microm2 s(-1) in the cytosol and 56 microm2 s(-1) in aqueous media. As in the case of dextrans of the same hydrodynamic radius, its mobility is hindered by both the crowding of the fluid phase of the cytoplasm and the screening effect due to myofilaments. A fraction of creatine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…Several studies have found that D of Mb in muscle fibers is about 1/6 to 1/10 of that in aqueous solution (Baylor and Pape, 1988;Jurgens et al, 1994;Papadopoulos et al, 1995;Papadopoulos et al, 2000;Papadopoulos et al, 2001). Measurements of protein diffusion in skeletal muscle from frog (Maughan and Lord, 1988;Maughan and Godt, 1999) and cultured mammalian fibers (Arrio-Dupont et al, 1997;Arrio-Dupont et al, 2000) yielded D values that were minimally 1/3 lower than that in water, and in many cases much more dramatically reduced. Analyses of the influence of hydrodynamic radius on the D values of macromolecules demonstrated that for both proteins , 1996) the difference between D in the sarcoplasm and D in water increased with molecule size, until in the largest proteins D was essentially negligible.…”
Section: The Intracellular Environment Of Muscle Has Characteristics mentioning
confidence: 99%
“…Several studies have found that D of Mb in muscle fibers is about 1/6 to 1/10 of that in aqueous solution (Baylor and Pape, 1988;Jurgens et al, 1994;Papadopoulos et al, 1995;Papadopoulos et al, 2000;Papadopoulos et al, 2001). Measurements of protein diffusion in skeletal muscle from frog (Maughan and Lord, 1988;Maughan and Godt, 1999) and cultured mammalian fibers (Arrio-Dupont et al, 1997;Arrio-Dupont et al, 2000) yielded D values that were minimally 1/3 lower than that in water, and in many cases much more dramatically reduced. Analyses of the influence of hydrodynamic radius on the D values of macromolecules demonstrated that for both proteins , 1996) the difference between D in the sarcoplasm and D in water increased with molecule size, until in the largest proteins D was essentially negligible.…”
Section: The Intracellular Environment Of Muscle Has Characteristics mentioning
confidence: 99%
“…It is beyond the scope of this review to discuss all mathematical models in detail, but we shall mention some biologically important parameters determining diffusion of soluble and membrane-bound molecules. Unrestricted diffusion of a particle in a free-volume model is described by the Stokes-Einstein formula 6 : D = kT/6πηR h which correlates the hydrodynamic behaviour of a sphere with the absolute temperature T, the viscosity of the solution η, the Boltzmann constant k and the hydrodynamic radius of the particle R h . Because the local absolute temperature is hardly affected by bleaching 7 , and the viscosity of water and cytosol are relatively constant under experimental conditions, D is determined mainly by R h .…”
Section: Quantitative Photobleachingmentioning
confidence: 99%
“…For instance, (5-enolase has a hydrodynamic radius of about 4 nm and diffusion coefficient in buffer Do = 56 pm2 s ~1. The diffusion coefficient in the cytosol of muscle cells is reduced to D = 13.5 pm 2 s _l [31]. Assume that the muscle cell has a characteristic radius of L = 25 nm (the typical values for the intracellular environment are L = 10-50nm) [10,[32][33][34][35][36][37], In Fig.…”
Section: Problem Statementmentioning
confidence: 99%